TEACHING SPEAKING STRATEGIES TO BEGINNERS - May Melendez, Rosa Adriana; Quijano Zavala, Gandy Griselda; Mendez, Rafael Ferrer (European Scientific Journal, ESJ, 2014)
In our experience as language teachers, speaking has always been the most challenging skill for most of our freshman students, at the Foreign Language Bachelor Degree at the Facultad de Ciencias Educativas in the Universidad Autónoma del Carmen. Despite the fact that various oral activities including strategies are implemented in the classroom, it is difficult to monitor each student’s progress. For that reason it was decided to invite some students to develop extracurricular sessions. During these sessions, they could practice the use of speaking strategies: Fillers, circumlocution, asking for clarification and expressing not understanding. Our main objective was to train the students on these basic speaking strategies so that they could use them regularly. The methodology to develop the sessions consisted in three stages: 1) a pre-task to know the participants’ previous knowledge of speaking strategies, 2) the training sessions, which were taught through formal instruction and practice in oral tasks and, 3) a post task to show if the frequency of strategy use increased after instruction. In order to analyze the progress of the participants, a questionnaire to collect previous knowledge about the students’ oral strategies, and a check list to analyze the video recorded sessions were used. The results from the post task showed there was an increase in the use of the strategies. Satisfactorily, the students showed more confidence when communicating or expressing themselves orally.